Agrarian sector of Ukraine in the global world - Lupenko, Y. (Acta Agraria Debreceniensis, 2013)
Characterization of Ukraine as a “bread basket” for the world have been done. In our study using database of State statistical service of Ukraine and FAO we showed changes of harvest areas and volume of production of cereals and protein-oil crops during this century.As a result we showed that Ukraine has increased its share in the world gross harvest of cereals up to 2.17% and protein-oil crops up to 3.4%. Each economically active agrarian produced 22.6 tons of cereals and 3.5 tons of protein-oil crops, increasing this index in comparing to 2000 in 11 and 12 times accordingly.Ukraine has a great potential for increasing crop production because of use genetic potential of varieties only for 60–70%. Here are shown changes in cattle, poultry breeding and dynamic of livestock production. We also included export of cereals and livestock production.